Durabilidade de argamassas submetidas ao ataque de sulfatos : efeito da adição da nanosílica - Schmalz, Rosana (2018)
Durability is one of the characteristics to be considered in design and projects of concrete structures as it is related to the useful life of buildings. Among the aggressive agents most damaging to the concrete are sulfate ions, both internal and external, that when in contact with the cement hydration products, cause expansion and cracking of the cementitious matrix. The purpose of this work was to produce more durable cementitious materials against the sulfate attack, with the use of nanosilica, a mineral addition with a lower particle size than the silica fume, which reacts chemically and physically in the hydration reactions of the cement. For this purpose, 1: 3.20 (cement: sand) mortar specimens were tested, two water/binder ratios (0.40 and 0.50) and three colloidal nanosilica contents (1, 5 and 10%). In addition, its effect was evaluated in combination with the silica fume. The mortars mechanical and physical properties were evaluated by means of mechanical strength tests and water absorption by capillarity, and their durability against the sulfate attack by means of dimensional variation tests, chemical and microscopic analyzes. Sulfate attacks were carried out externally, by immersing the test specimens in sodium sulfate solution (10%), and internally by using a sulfate-containing mixing water (3%). In addition, some mortars were subjected to heat cure at 85ºC, in order to verify the occurrence of an internal sulfate attack, due to high temperatures. In general, the results indicated that the nanosilica contributed to the increase of the compressive strength and, mainly, to the reduction of the capillary absorption coefficients of the mortars, due to its filler and pozzolanic effects. Regarding the durability against sulfate attack, both external and internal, it was not possible to verify the positive effects of nanosilica on mortars subjected to wet curing, since during the 91 days of the experiment no evidence of expansion was observed. As for mortars subjected to heat curing, the 10% nanosilica addition was efficient in mitigating delayed ettringite formation (DEF), preventing expansion and cracking. Finally, it was concluded that the nanosilica addition results in positive effects on the cementitious matrix microstructure, reducing its permeability and, consequently, increasing its durability against aggressive agents.